A comparison of early fixation of distal radius fractures versus late corrective osteotomy of distal radius malunion. Issue 12 (19th October 2022) - Gouk, Conor; Bairstow, Melissa; Thomas, Michael; Tan, Ezekiel; Taylor, Fraser; Bindra, Randy
Abstract: Background: Fractures of the distal radius are common. Closed reduction and moulded casting is often the first line treatment. Malunion after casting is not uncommon and can lead to discussion on acute surgical fixation versus delayed corrective osteotomy if symptomatic. However, it is unclear if late surgery will provide similar outcomes as early intervention. Methods: We performed a single centre, age matched, case series comparison study, comparing outcomes of patients who had undergone early fixation (ORIF) versus those who had undergone late corrective osteotomy (CO) following distal radius fracture. Results: Twenty‐six patients were available for review, 13 in each group. Fracture patterns were similar. Reviewing CO versus ORIF; patients achieved a mean DASH; 22 versus 18 ( P = 0.355), PRWE; 35 versus 26 ( P = 0.237), and VAS 2 versus 2 ( P = 0.490). Grip strength was significantly better in those who had undergone ORIF; 2% versus −22% ( P ≤ 0.001). Range of motion was generally better with primary fixation but of doubtful clinical importance, reviewing CO versus ORIF; Flexion 46° versus 60° ( P = 0.045), extension 55° versus 64° ( P = 0.137), pronation 73° versus 85° ( P = 0.078), supination 84° versus 84° ( P = 0.747), flexion/extension arc 101 versus 124 ( P = 0.017), ulnar/radial deviation arc 42° versus 59° ( P = 0.01), pronation/supination arc 157° versus 168° ( P = 0.118). Ulnar variance was significantly improved in the ORIF group; +0.5 mm versus +2 mm in the CO group ( P = 0.023). Radial inclination, radial height and volar tilt were not significantly different between either group. Conclusion: Our findings suggest that patient measured outcome of corrective osteotomy is not inferior to early internal fixation. Level of Evidence: III (Case Series Comparison). Abstract : Fractures of the distal radius are common, however in circumstances whereby the patient may require surgical intervention, it is unclear if necessitated late surgery will provide similar outcomes as early intervention. We performed a single centre, age matched, retrospective cohort comparison study, comparing outcomes of patients who had undergone early fixation (ORIF) versus those who had undergone late corrective osteotomy (CO) following distal radius fracture. Our findings suggest that the patient measured outcome of corrective osteotomy is comparable with early internal fixation.